The Global Success of Mycobacterium tuberculosis Modern Beijing Family Is Driven by a Few Recently Emerged Strains - Chendi Zhu; Tingting Yang; Jinfeng Yin; Hui Jiang; Howard E. Takiff; Qian Gao; Qingyun Liu; Weimin Li (Microbiology Spectrum, 2023)
ABSTRACT Strains of the Mycobacterium tuberculosis complex (MTBC) Beijing family aroused concern because they were often found in clusters and appeared to be exceptionally transmissible. However, it was later found that strains of the Beijing family were heterogeneous, and the transmission advantage was restricted to sublineage L2.3 or modern Beijing. In this study, we analyzed the previously published genome sequences of 7,896 L2.3 strains from 51 different countries. Using BEAST software to approximate the temporal emergence of L2.3, our calculations suggest that L2.3 initially emerged in northern East Asia during the early 15th century and subsequently diverged into six phylogenetic clades, identified as L2.3.1 through L2.3.6. Using terminal branch length and genomic clustering as proxies for transmissibility, we found that the six clades displayed distinct population dynamics, with the three recently emerged clades (L2.3.4 to L2.3.6) exhibiting significantly higher transmissibility than the older three clades (L2.3.1 to L2.3.3). Of the Beijing family strains isolated outside East Asia, 83.1% belonged to the clades L2.3.4 to L2.3.6, which were also associated with more cross-border transmission. This work reveals the heterogeneity in sublineage L2.3 and demonstrates that the global success of Beijing family strains is driven by the three recently emerged L2.3 clades. IMPORTANCE The recent population dynamics of the global tuberculosis epidemic are heavily shaped by Mycobacterium tuberculosis complex (MTBC) strains with enhanced transmissibility. The infamous Beijing family strain stands out because it has rapidly spread throughout the world. Identifying the strains responsible for the global expansion and tracing their evolution should help to understand the nature of high transmissibility and develop effective strategies to control transmission. In this study, we found that the L2.3 sublineage diversified into six phylogenetic clades (L2.3.1 to L2.3.6) with various transmission characteristics. Clades L2.3.4 to L2.3.6 exhibited significantly higher transmissibility than clades L2.3.1 to L2.3.3, which helps explain why more than 80% of Beijing family strains collected outside East Asia belong to these three clades. We conclude that the global success of L2.3 was not caused by the entire L2.3 sublineage but rather was due to the rapid expansion of L2.3.4 to L2.3.6. Tracking the transmission of L2.3.4 to L2.3.6 strains can help to formulate targeted TB prevention and control.